The preoperative neutrophil-to-lymphocyte ratio predictive value for survival in patients with brain metastasis - Helder Picarelli; Vitor Nagai Yamaki; Davi Jorge Fontoura Solla; Iuri Santana Neville; Alexandra Gomes dos Santos; Bruno Spindola Amaral Garcia de Freitas; Calvin Diep; Wellingson Silva Paiva; Manoel Jacobsen Teixeira; Eberval Gadelha Figueiredo (Arquivos de Neuro-Psiquiatria)
Background The neutrophil-to-lymphocyte (NLR), monocyte-to-lymphocyte (MLR), platelet-to-lymphocyte ratio (PLR), and red blood cell distribution width (RDW) have been previously studied as predictors of survival in different malignancies.